ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Diana, Diana; Harahap, Baru (SCIENTIA JOURNAL, 2020)
This research aims to determine the potential of bankruptcy by using Altman Z-Score model in textile and garment company listed on Indonesia Stock Exchange period 2015- 2019. In this study used a quantitative descriptive approach. This research uses the Purposive sampling method by assigning certain criteria in selecting research samples so that 6 companies are made samples. The data collection techniques used are the documentation and the analytical techniques used are models of the Altman Z-Score modifications. The equation of the Altman Z-Score model is Z"=6,56 X1 + 3,26 X2 + 6,72 X3+ 1,05 X4. Then classified into the category of not going bankrupt, gray areas and going bankrupt based on the cut-off value of the Z-score altman model namely: If Z is greater than 2.60 then the company is categorized as not bankrupt, if Z is between 1.1 and 2.60 then the company including the gray area category if Z is less than 1.1, the company is bankrupt. The results showed that there were 2 companies that were predicted to be potentially bankrupt, 2 companies that were predicted in gray or prone to bankrupt conditions, and 2 companies that were predicted to be in not bankrupt or healthy conditions.